THE RELATIONSHIP BETWEEN BIOSECURITY IMPLEMENTATION AND MORBIDITY AND MORTALITY IN PIGS IN PAYANGAN DISTRICT, GIANYAR BALI - Ni Made Wida Rieke Pitaloka; I Ketut Suada (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Until now, pig farming in Bali has a very important role in supporting the economy of the local community. However, the management of pig farms in Bali cannot be separated from the obstacles faced, namely the outbreak of disease agents. Biosecurity is considered a fundamental cornerstone of all disease control programs. The aim of this research is to determine the relationship between the application of biosecurity and morbidity and mortality. This research uses an observational design. The number of respondents used in this research was 40 breeders. Data collection in this research was carried out by conducting surveys and interviews with farmers regarding the implementation of biosecurity and the incidence of morbidity and mortality on the farms they own. The data obtained is presented in tabular form. Chi-square test analysis was carried out to compare data from farms that implemented biosecurity with those that did not implement biosecurity. The research results found that farms that implemented biosecurity experienced 6 incidents of morbidity and 3 incidents of mortality. Meanwhile, farms that did not implement it experienced 15 morbidity incidents and 11 mortality incidents. The conclusion of this research is that implementing biosecurity on a farm can reduce the incidence of morbidity and mortality. The advice that can be given is that preventive efforts such as implementing biosecurity should not only be carried out if a case has occurred but must continue to be carried out on an ongoing basis.